HUBUNGAN ANTARA KEKUATAN OTOT LENGAN DENGAN JAUHNYA PUKULAN DALAM PERMAINAN KASTI PADA SISWA PUTRA KELAS V SDN 1 RARANG LOTIM TAHUN PELAJARAN 2014/2015 - Rahim, Abdul (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
On learning in elementary school, physical education teachers also teach the game of rounders that required skills in performing basic techniques owned a baseball game. One of them is a blow. How blow away in a game of rounders can affect the game. When a player can hit the ball a long distance, then the other player can return to the home resulting in a point or points for the tim.Rumusan problem in this study is whether there is relationship between the remoteness Arm Muscle Strength Punch in Kasti on Student Games Men's Class SDN 1 Rarang Lotim in the academic year 2014/2015? the aim of the research was to find out relationship between the remoteness Arm muscle Strength Punch in Kasti on student Games Men's Class V SDN 1 Rarang Lotim in the academic year 2014 / 2015.Populasi in this study were all students class V SDN 1 Rarang Lotim Academic Year 2014/2015 amounting to 12 students, while the researchers used a sample of 100% so that the sampling technique used in this study adalahstudi populasi. Obtain the data necessary to support the success of the research, it is necessary a method for data collection , In accordance with the objectives of this study, the method used is the test method works to obtain data on the arm muscle strength using the push-ups for one minute and blow away in a game of rounders measured using meteran.Dari results of data analysis obtained by value "rxyhitung amounted to 0.052, while the magnitude of the numbers r table with a significant level of 5% and N = 12 is 0.576. This means that the count r is smaller than r table (0.052 <0.576) so it concluded that "there is no relationship between the strength of the arm muscles to blow away in the game of baseball in grade male student V SDN 1 Rarang Lotim in the academic year 2014/2015.